2016
DOI: 10.1002/hep.28357
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/AKT/mTOR‐dependent stabilization of oncogenic far‐upstream element binding proteins in hepatocellular carcinoma cells

Abstract: Transcription factors of the far-upstream element-binding protein (FBP) family represent cellular pathway hubs, and their overexpression in liver cancer (hepatocellular carcinoma [HCC]) stimulates tumor cell proliferation and correlates with poor prognosis. Here we determine the mode of oncogenic FBP overexpression in HCC cells. Using perturbation approaches (kinase inhibitors, small interfering RNAs) and a novel system for rapalog-dependent activation of AKT isoforms, we demonstrate that activity of the phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 41 publications
4
47
1
1
Order By: Relevance
“…Of note, the present study demonstrated that AKT mRNA was decreased in TRB3-knockdown MHCC97H cells. This was in contrast to the findings of a previous study, which suggested that the level of ATK mRNA expression may be upregulated under TRB3 suppression (10). This may be attributed to the specificity of the tumor type.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Of note, the present study demonstrated that AKT mRNA was decreased in TRB3-knockdown MHCC97H cells. This was in contrast to the findings of a previous study, which suggested that the level of ATK mRNA expression may be upregulated under TRB3 suppression (10). This may be attributed to the specificity of the tumor type.…”
Section: Discussioncontrasting
confidence: 99%
“…Conversely, TRB3 inhibits activation of protein kinase B (AKT) by binding with its threonine or serine activated site, which results in the activation of the downstream signal to induce cell apoptosis (7,8). Furthermore, much of the research in the previous two decades has indicated that the AKT signaling pathway is closely associated with the occurrence and development of hepatic carcinoma (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, de novo lipogenesis is activated downstream of the Akt/mTOR pathway, one of the most common signaling pathways altered in cancer. Forced activation of Akt/mTOR induces liver cancer [160, 161], a process mediated at least in part by activation of FASN [155, 156]. Consistently, inactivation of FASN was recently shown to completely inhibit Akt-driven HCC in mice [158].…”
Section: Ppars and Mitochondrial Dysfunction From Nafld To Hccmentioning
confidence: 99%
“…Hyperactive AKT‐mTOR signaling is a common phenomenon in HCC . Activation of AKT and mTOR is critical for HCG in various common HCC models in mice . However, a recent clinical trial did not achieve desirable endpoints on the rapamycin analog, everolimus, in advanced HCC patients .…”
mentioning
confidence: 99%
“…(20,21) Activation of AKT and mTOR is critical for HCG in various common HCC models in mice. (22)(23)(24)(25) However, a recent clinical trial did not achieve desirable endpoints on the rapamycin analog, everolimus, in advanced HCC patients. (26,27) Therefore, identifying new treatment strategies, such as combination therapy, is necessary for improving the efficacy of rapamycin and rapamycin analogs in order to bring mTOR-targeted therapies into the clinic.…”
mentioning
confidence: 99%